Cardiovascular Health Assessment in Artisanal Divers in the Lagos Region, Chile - Alex Véliz Burgos; Anita Dörner Paris; Raquel Pereira Berrios; Edgardo González Sierra (Revista Finlay)
Foundation: cardiovascular health plays a crucial role in the functional capacity and overall well-being of individuals engaged in intense and prolonged physical activities, such as artisanal diving. Several studies highlight the importance of monitoring parameters such as blood pressure in artisanal divers. Objective: to evaluate the cardiovascular health status of Chilean artisanal divers. Methods: a study was conducted to assess the cardiovascular health of artisanal divers in southern Chile using a quantitative methodological approach that included blood pressure measurement, body mass index, and a health survey. Participants were selected using non-probability sampling. The focus was on active artisanal divers from specific coastal communities. Fifty-five divers were evaluated, with a mean age of 53.7 years (SD = 11.9 years). The data obtained from these measurements and surveys were recorded and stored in an Excel database and then analyzed using SPSS software. Results: most of the evaluated divers had elevated blood pressure, suggesting a concerning prevalence of hypertension in this population. Furthermore, a high body mass index was observed in most individuals, which is an additional risk factor for cardiovascular disease. Conclusions: the evaluated divers had elevated blood pressure, and a high body mass index was observed in most individuals, which is an additional risk factor for cardiovascular disease.